All these things I've done - Zevin, Gabrielle (New York : Farrar Straus Giroux, 2011)
In a future where chocolate and caffeine are contraband, teenage cellphone use is illegal, and water and paper are carefully rationed, sixteen-year-old Anya Balanchine finds herself thrust unwillingly into the spotlight as heir apparent to an important New York City crime family.
Keywords: Organized crime -- Fiction; Celebrities -- Fiction; High schools -- Fiction; Schools -- Fiction; Teenage girls -- Fiction; Sixteen-year-old girls -- Fiction; Teenage boy/girl relations -- Fiction; Chocolate -- Fiction; Family life -- New York (State) -- New York -- Fiction; New York (N.Y.) -- Fiction; Science fiction; Organized crime -- Juvenile fiction; Celebrities -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Families -- New York (State) -- New York -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Science fiction